2023
DOI: 10.1093/braincomms/fcad177
|View full text |Cite
|
Sign up to set email alerts
|

Markers of limbic system damage following SARS-CoV-2 infection

Abstract: Alterations of the limbic system may be present in the chronic phase of SARS-CoV-2 infection. Our aim was to study the long-term impact of this disease on limbic system-related behaviour and its associated brain functional connectivity, according to the severity of respiratory symptoms in the acute phase. To this end, we investigated the multimodal emotion recognition abilities of 105 patients from the Geneva COVID-COG cohort 223 days on average after SARS-CoV-2 infection (diagnosed between March 2020 and May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 67 publications
(91 reference statements)
0
11
0
Order By: Relevance
“…First, our results confirmed that the neurocognitive consequences of SARS-CoV-2 infection go beyond any effect of ICU hospitalisation. More specifically, neuropsychological deficits at 6–9 and 12–15 months post-infection were found to be partially independent of the severity of the initial infection, thus supporting previous observations [ 1 , 6 , 9 , 10 , 43 45 ]. Moreover, concerning changes in the neuropsychological deficits, the results of our assessment at 12–15 months indicated a normalisation of attentional deficits in the moderate subgroup, the persistence of memory and logical reasoning symptoms in both the moderate and severe subgroups, and deteriorations in both instrumental functioning and executive functions in the moderate and severe subgroups.…”
Section: Discussionsupporting
confidence: 88%
“…First, our results confirmed that the neurocognitive consequences of SARS-CoV-2 infection go beyond any effect of ICU hospitalisation. More specifically, neuropsychological deficits at 6–9 and 12–15 months post-infection were found to be partially independent of the severity of the initial infection, thus supporting previous observations [ 1 , 6 , 9 , 10 , 43 45 ]. Moreover, concerning changes in the neuropsychological deficits, the results of our assessment at 12–15 months indicated a normalisation of attentional deficits in the moderate subgroup, the persistence of memory and logical reasoning symptoms in both the moderate and severe subgroups, and deteriorations in both instrumental functioning and executive functions in the moderate and severe subgroups.…”
Section: Discussionsupporting
confidence: 88%
“…decrease in episodic memory, objective cognitive decline, weakened attention and fatigue. 21-23 This hypothesis is strengthened by neuroimaging studies that report significant loss in limbic functional connectivity and grey matter volume. 15 , 18-20 , 28 , 50-53 Microstructural alterations in the tracts involved in the limbic system, as observed in our study, could be a precursor to these functional deficits.…”
Section: Discussionmentioning
confidence: 97%
“… 54 Moreover, microstructural damage in the limbic white matter could be a precursor to the widely reported functional deficits like decline in episodic memory, attention and cognitive abilities. 21-23 In some tracts, the observed increased myelination and axonal growth may represent the result of a compensatory or recovery mechanism in response to COVID-related damage to other tracts. Moreover, the observations of this study are also consistent with neurological case studies on COVID-19 patients and group-level studies conducted using DWI and other MRI modalities.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Cognitive impairment (e.g., attention or memory issues), commonly reported as “brain fog,” is highly prevalent in Long COVID, affecting approximately 80% of long haulers ( 11 ). Neuroimaging studies have detected damages in various limbic and associative brain regions following COVID-19 infection, likely indicative of neuroinflammation and possible neurodegeneration ( 12 , 13 ). Notably, chronic loss of smell correlates with cognitive decline and is an early predictor of Alzheimer’s disease ( 14 ).…”
Section: Introductionmentioning
confidence: 99%